Liver Stiffness and Steatosis Measurements with iLivTouch and FibroScan: A Comparative Study - Özercan, Mübin; Melekoğlu Ellik, Zeynep; Parmaksız, Ayhan; Gümüşsoy, Mesut; Duman, Serkan; Örmeci, Necati (Turkish Journal of Gastroenterology, 2024)
Background/Aims: The presence of liver fibrosis is the most important indicator of progression to cirrhosis. Noninvasive measurement of liver stiffness is crucial for detecting fibrosis. Vibration-controlled transient elastography is one of the most useful methods for this purpose. We aimed to compare the liver stiffness and steatosis measurements with iLivTouch© and the FibroScan© elastography devices Materials and Methods: Two hundred thirty-seven consecutive adult patients with chronic hepatitis were included in the study. The liver stiffness and steatosis were measured with iLivTouch and FibroScan on the same day. Thirty-one patients had liver biopsies on the same day with elastography procedures. The diagnostic performances of iLivTouch and FibroScan were compared to aspartate aminotransferase to platelet ratio index (APRI), Fibrosis-4 (FIB-4), and nonalcoholic fatty liver disease fibrosis score (NFS). Results: The liver stiffness measurements obtained using iLivTouch and FibroScan had median value of 10.3 (ranging from 2.9 to 46.3) and 7.2 (ranging from 2.5 to 75), respectively. The mean steatosis measurements using ultrasound attenuation parameter with iLivTouch were 245.51 ± 45.79, while the mean controlled attenuation parameter measurements using FibroScan were 259.37 ± 75.0. In subgroup analysis, the AUC of iLivTouch on detecting signiicant fibrosis [0.83, (P = .002)] was minimally higher than other noninvasive methods [0.82 for NFS (P = .003), 0.80 for FibroScan (P = .006), 0.68 for FIB-4 (P = .089), and 0.53 for APRI (P = .76)]. Conclusion: The stiffness and steatosis measurements with iLivTouch and FibroScan were not similar. The accuracy of iLivTouch in detecting significant and advanced fibrosis was minimally higher. Large clinical trials are necessary to support these findings. Cite this article as: Özercan M, Melekoğlu Ellik Z, Parmaksız A, Gümüşsoy M, Duman S, Örmeci N. Liver stiffness and steatosis measurements with iLivTouch and FibroScan: A comparative study. Turk J Gastroenterol. 2024;35(8):634-642.